The Impact of Comprehensive and Progressive Trans-Pacific Partnership Free Trade Agreement on Indonesian Economy - Aris Munandar; Annisa Nur Salam; M. Taufik Ridho (Global Review of Islamic Economics and Business, 2020)
Islamic law is inclined toward free trade and condemned imposing tariffs on trade with other states. Even when tariffs were imposed, they were imposed based on reciprocity. The Comprehensive and Progressive Trans-Pacific Partnership (CPTPP) is a free trade agreement to realize tariff elimination. CPTPP was signed by 11 countries in Santiago, Chile, on March 8, 2018, and this renewed agreement attracted Indonesia to join. This study analyzes the possible impact of CPTPP implementation on the Indonesian economy using the Global Trade Analysis Project (GTAP) model. We conduct a simulation to evaluate the impact of CPTPP on the Indonesian economy. The results show that the implementation of CPTPP leads to an increase in the real GDP and welfare of Indonesia. Also, the study found that CPTPP is beneficial to members. These results generally justify the elimination of tariffs promoted by Islamic law.